2022
DOI: 10.3390/ani12162151
|View full text |Cite
|
Sign up to set email alerts
|

“Emotional Proximity” and “Spatial Proximity”: Higher Relationship Quality and Nearer Distance Both Strengthen Scratch Contagion in Tibetan Macaques

Abstract: Behavioral contagion has been defined as a phenomenon in which an unlearned behavior automatically triggers a similar behavior in others. Previous studies showed that a behavioral contagion might have the function of strengthening social relationships, promoting group coordination and maintaining social cohesion. However, so far, there are few studies investigating the correlation between contagious scratching and social bonding. Tibetan macaques (Macaca thibetana) live in multi-male and multi-female cohesive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 58 publications
(88 reference statements)
0
3
0
Order By: Relevance
“…Previous studies have shown that videos or pictures of people scratching can induce scratching behavior in healthy individuals 35 . Besides humans, contagious scratching has been observed in few other species, including rhesus macaques (Macaca mulatta) 37 , Japanese monkeys (M. fuscata) 38 , Tibetan macaques (M. thibetana) 39 and spider monkeys 33 . A study on mice, instead, failed to detect contagious scratching 40 .…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that videos or pictures of people scratching can induce scratching behavior in healthy individuals 35 . Besides humans, contagious scratching has been observed in few other species, including rhesus macaques (Macaca mulatta) 37 , Japanese monkeys (M. fuscata) 38 , Tibetan macaques (M. thibetana) 39 and spider monkeys 33 . A study on mice, instead, failed to detect contagious scratching 40 .…”
Section: Introductionmentioning
confidence: 99%
“…In humans, scratching is triggered by listening to the word “itching” 38 or itch-related sounds 39 , and by observing others scratching 40 42 . In non-human primates, contagious scratching has been shown in captive orangutans 37 , captive Japanese macaques ( Macaca fuscata 43 ), wild Tibetan macaques ( M. thibetana 44 ) and captive rhesus macaques ( M. mulatta 45 ). As in the case of yawning, however, there is no evidence for scratching contagion in Platyrrhines yet (captive common marmosets 33 ).…”
Section: Introductionmentioning
confidence: 99%
“…In humans, scratching is triggered by listening to the word "itching" [38] or itch-related sounds [39], and by observing others scratching [40][41][42]. In non-human primates, contagious scratching has been shown in orangutans [37], Japanese macaques (Macaca fuscata [43]), Tibetan macaques (M. thibetana [44]) and rhesus macaques (M. mulatta [45]). As in the case of yawning, there is no evidence for scratching contagion in Platyrrrhines (for negative results in common marmosets, see [30]).…”
Section: Introductionmentioning
confidence: 99%